Occupational therapy students' experience with using a journal in fieldwork and factors influencing its use. Issue 5 (3rd September 2018) - Craig-Duchesne, Cloé; Rochette, Annie; Scurti, Sylvie; Beaulieu, Johanne; Vachon, Brigitte
ABSTRACT: The aims of this study were to (1) describe journal use in occupational therapy fieldwork and students' preferences regarding use, and (2) document factors that influence this use. We used a mixed method design: Quantitative data were collected through an online survey developed by the research team, and qualitative data from afocus group. Respondents were in the thirdyear of the professional bachelor's‒master's continuum curriculum in occupational therapy. Descriptive and content analyses were used. We found that most of the 32 students who completed the survey used atraditional structured journal, daily at the beginning of fieldwork and less often at the end. The majority spent less than 30 minutes completing the journal during and outside fieldwork time. For 19/32 participants, the preceptor's feedback was received weekly via different means. This use did not reflect participants' preferences as 48% of the students considered journal use helpful in fostering reflective practice. Eight influencing factors emerged from the focus group (n = 4): student's communication skills, student's communication preferences, journal structure, frequency of use, student's workload, and three other factors related to the social environment. In conclusion, journal use and students' preferences vary and are influenced by different personal and contextual factors. To optimize journal use, areflective approach is desirable.